Drug-specific Treg cells are induced during desensitization procedure for rituximab and tocilizumab in patients with anaphylaxis - Alessandra Vultaggio (Nature Portfolio, 2021)
Abstract Biologic agents (BA) are able to induce an adaptive immune response in a proportion of exposed patients with the onset of anti-drug antibodies (ADA), which are usually responsible for hypersensitivity reactions (HR). Drug desensitization (DD) for BA allows transient clinical tolerance to the drug in reactive patients. The paper aimed to analyse the modification of drug-specific immune responses along DD in two patients with previous ADA-mediated HR (anaphylaxis) to rituximab and tocilizumab. The in vivo and in vitro assays of humoral and cellular response to drugs were carried out in a longitudinal manner throughout the DD cycles. We observed a progressive decrease of the pre-procedure ADA titer with negativization during the DD cycles in both patients. The monitoring of the drug-specific effector cell response showed the decrease in the BA-induced proliferation, while T cell response to unrelated antigens resulted unmodified along the DD cycles. Lastly, the increase of circulating drug-specific Treg cells mainly producing IL-35 were shown during the DD treatment. This study provides evidence that DD treatment to two BA inhibits humoral and cellular anti-drug response by increasing regulatory T cells and cytokines in an antigen-restricted manner. These modifications could contribute to the safety of the procedure.